The Identifikasi Titik Kritis Kehalalan dalam Produk Turunan Hewani: Pendekatan Sistematik untuk Keamanan Konsumen - Sumarlin, Abdul; Parakkasi, Idris; Muthiadin, Cut; Umar, Rahmawati (AkMen JURNAL ILMIAH, 2024)
This research aims to identify critical halal points in animal derivative products to ensure the safety of Muslim consumers and support the economic optimization of halal management in the global food industry. By using a literature study method, this research highlights the importance of halal raw materials and production processes, which not only fulfill religious demands but also increase market competitiveness. The halal identification process involves checking raw materials, production processes, additives, storage, transportation and certification. The tipping point is found in bone, skin, fur, fat, blood, offal, placenta, milk, egg and fish derivative products, all of which require halal verification based on Islamic law. Animal-based flavorings are also analyzed to ensure there is no contamination from non-halal animals. In conclusion, every stage of production of animal derivative products must be thoroughly checked to ensure halalness, support business strategies, and increase consumer confidence in the global market. Key words: Halal raw materials and production processes, Animal derivative products, Identification of halal critical points